Optimization of process conditions for the development of rice milk by using response surface methodology - P Plengsaengsri; T Pimsuwan; T Wiriya-Aree; J Luecha; S Nualkaekul; P Deetae (My University, 2019)
Abstract Rice milk is a dairy product alternative for who are allergenic milk protein, lactose and concern about cholesterol. Unlike cow’s milk, rice milk contains little protein but has a higher carbohydrate content. The purpose of this research was to study the optimal condition to develop rice milk nutritionally equivalent to cow milk with consumer acceptability. In this study, we used rice protein concentrate, rice flour, rice bran oil, sugar and calcium lactate as ingredients. Firstly, the selection of enzymes for rice protein hydrolysis was carried out and neutrase had high degree of hydrolysis with the highest consumer acceptability (p<0.05). Response surface methodology (RSM) base on central composite design was then employed to investigate the optimum condition with three independent variables: enzyme: protein ratios, speeds and times of homogenization. Our results reveal that the experimental variables significantly affected the color and sensory attributes. The optimum condition for rice milk production was found to be 16000 rpm,20 minutes of homogenization and 1:40 (w/w). The milk produced from this condition had protein 3.14 %, fat 3.28%, fiber 0.45%, ash 0.44% moisture 86.85% and carbohydrate 5.84%, which was similar to the nutritional value of cow’s milk. The developed product showed good nutritional and sensory characteristics and this could be used for the development of commercial rice milk beverage after conducting appropriate scale up and pilot plant study.
Keywords: Broken rice; Homogenization; Central composite design; Rice bran oil; Cow milk; Probiotics and Fermented Foods